The stock market crash of 1929 - Millichap, Nancy (New York : Maxwell Macmillan International, 1994)
An examination of the events leading up to and following the collapse of the stock market in 1929.
Includes bibliographical references (p. 92-94) and index.
Booklist.
Horn Book.
Wilson's Junior High School.
7.5
5-8
Keywords: New York Stock Exchange -- Juvenile literature; New York Stock Exchange -- History; New York Stock Exchange -- History; Depressions -- 1929 -- United States -- Juvenile literature; Depressions -- 1929.; Depressions; United States -- Economic conditions -- 1918-1945 -- Juvenile literature; United States -- Economic conditions -- 1918-1945.; United States -- Economic conditions